REKAYASA SISTEM PRESENSI KLINIK KESEHATAN BERBASIS APLIKASI MOBILE - I Made Cakra Pustaka1; I Ketut Putra Swastika; I Kadek Agung Bagus Satria Bumi Kelana; Made Sudarma; I Made Arsa Suyadnya; Duman Care Khrisne (Program Studi Teknik Elektro UNUD, 2025)
Manual attendance systems in health clinics are often ineffective, reducing service quality, and increasing operational costs. This study designed an integrated digital attendance system with a mobile application for medical personnel and an admin website aimed at improving the efficiency and accuracy of attendance management. Development followed the Waterfall SDLC model, while testing included Black-Box Testing, Cognitive Walkthrough (CW), and System Usability Scale (SUS). The mobile application supports in-clinic/out-of-clinic attendance (Wi-Fi validation, geolocation, selfie photos, documents), leave requests, work schedules, attendance recaps, and pay slips. The admin website facilitates employee data management, attendance and leave validation, work schedule creation, and salary and attendance recaps. Black-Box Testing results showed success in all functional scenarios; CW recorded 96% effectiveness (mobile) and 98% (website) with very fast efficiency; SUS scores of 76.42 and 76.07, respectively, indicating good usability; and API testing proved smooth data integration. This system has been proven to be functional, effective, efficient, and ready to be implemented in health clinics.